2012
DOI: 10.1111/j.1365-2672.2012.05407.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Candida albicansaction of the glyco-protein complex purified from metabolites of gut bacteriumRaoultella ornithinolyticaisolated from earthwormsDendrobaena veneta

Abstract: Aims: The aim of our research was to isolate the compounds from the metabolites of Raoultella ornithinolytica with the activity against Candida albicans and to analyse the action of the compounds on the metabolic activity and morphology of the fungus cells. Methods and Results: The effect of active protein fractions on the cell morphology, growth, and metabolic activity of C. albicans was analysed under a light microscope with Nomarski contrast and after staining with calcofluorwhite. The LIVE/DEAD Yeast Viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 38 publications
(37 reference statements)
1
26
0
Order By: Relevance
“…In this context, FUN-1 has been used in the assessment of the toxic impact of organic and inorganic compounds on yeast metabolic activity (Fiolka et al 2012;ParisiDuchene et al 2006; Van der Heggen et al 2010). Before metal treatment, >97 % yeast cells were metabolically active and thus able to process and concentrate FUN-1 in the vacuole, as orange-red cylindrical intravacuolar structures (CIVS, FUN-1-positive cells) (Fig.…”
Section: Multiple Metals Disturbs Membrane Integrity In a Time-dependmentioning
confidence: 99%
“…In this context, FUN-1 has been used in the assessment of the toxic impact of organic and inorganic compounds on yeast metabolic activity (Fiolka et al 2012;ParisiDuchene et al 2006; Van der Heggen et al 2010). Before metal treatment, >97 % yeast cells were metabolically active and thus able to process and concentrate FUN-1 in the vacuole, as orange-red cylindrical intravacuolar structures (CIVS, FUN-1-positive cells) (Fig.…”
Section: Multiple Metals Disturbs Membrane Integrity In a Time-dependmentioning
confidence: 99%
“…11856. The SERS analysis confirmed that the compounds obtained are a protein and carbohydrate (Fiołka et al ., ). Our previous analysis performed using SDS/PAGE electrophoresis had shown that the complex obtained contained several high molecular weight proteins (with two main 65‐ and 68‐kDa bands), but after native electrophoresis, one band was observed on the gel.…”
Section: Resultsmentioning
confidence: 97%
“…After incubation of C. albicans cells with the PPC at the concentration of 5 μg mL −1 , the relative metabolic activity of the fungal cells was significantly decreased by 30% and by 35% after the treatment with 10 μg mL −1 (Fiołka et al ., ). Figure a2,b2 and c2 show metabolically active and inactive cells.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations